2020
DOI: 10.1111/1462-2920.15211
|View full text |Cite
|
Sign up to set email alerts
|

Genetic examination of the marine bacterium Pseudoalteromonas luteoviolacea and effects of its metamorphosis‐inducing factors

Abstract: Summary Pseudoalteromonas luteoviolacea is a globally distributed marine bacterium that stimulates the metamorphosis of marine animal larvae, an important bacteria–animal interaction that can promote the recruitment of animals to benthic ecosystems. Recently, different P. luteoviolacea isolates have been shown to produce two stimulatory factors that can induce tubeworm and coral metamorphosis; Metamorphosis‐Associated Contractile structures (MACs) and tetrabromopyrrole (TBP) respectively. However, it remains u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…Species of the genus Pseudoalteromonas are common within the marine environment and have been found associated with corals, sponges, seagrass surface and within molluscs (Romanenko et al, 2008). P. luteoviolacea (found in this study) is a globally distributed marine bacterium that can induce the metamorphosis of tubeworm and coral larvae (Alker et al, 2020) Finally, one OTU matching with Methylophaga thiooxydans was found in the present study within the seed microenvironments. Methanolconsuming bacteria are common in marine environments and include members of the genera Methylophaga and Methylobacter.…”
Section: Seed Microbiomesupporting
confidence: 65%
“…Species of the genus Pseudoalteromonas are common within the marine environment and have been found associated with corals, sponges, seagrass surface and within molluscs (Romanenko et al, 2008). P. luteoviolacea (found in this study) is a globally distributed marine bacterium that can induce the metamorphosis of tubeworm and coral larvae (Alker et al, 2020) Finally, one OTU matching with Methylophaga thiooxydans was found in the present study within the seed microenvironments. Methanolconsuming bacteria are common in marine environments and include members of the genera Methylophaga and Methylobacter.…”
Section: Seed Microbiomesupporting
confidence: 65%
“…113 Biochemical studies on the inducing strain P. luteoviolacea allowed for the identication of bacteriophage-tail-like proteins (T4-type phage tail assemblies) termed Metamorphosis Associated Contractile structures (MACs, 54), which are composed of contractile structures with outward-facing baseplates linked by tail bres and forming a dynamic hexagonal net. 109,114 Based on the hypothesis that MACs should cause puncturing of cell membranes, transcriptome studies on induced larvae were pursued, which revealed the effects of MACs on the gene regulation for tissue remodeling, innate immunity, and mitogenactivated protein kinase. 115 Here, the authors proposed signalling pathways through a p38 and c-Jun N-terminal kinase (JNK) and Mitogen-activated protein kinase (MAPK) pathways.…”
Section: Tubewormmentioning
confidence: 99%
“… H. symbiolongicarpus colonies were generously provided by the Nicotra laboratory at the University of Pittsburgh. Strains were isolated from single colonies cultured on artificial seawater-tryptone (ASWT) agar medium ( 1 ) at 28°C for 48 h and subsequently were cultured in SWT liquid medium at 28°C for 24 h. Species identity was confirmed by 16S rRNA gene sequencing. Strains were grown in the same manner as for the isolation for DNA extraction.…”
Section: Announcementmentioning
confidence: 99%